PHYSICAL CHARACTERIZATION OF 3D-PRINTED HIPS BOLUSES AT DIFFERENT THICKNESSES AND INFILL DENSITIES FOR RADIOTHERAPY - Faisal Ahlan Rizaldi; Sri Herwiningsih; Dionysius J.D.H. Santjojo; Luthfia Aqila Abrar (Universitas Mataram, 2026)
In external beam radiation therapy, conventional boluses have limitations in conforming to irregular skin surfaces, leading to the formation of air gaps between the skin surface and the bolus. The fabrication of a three-dimensional printed (3D-printed) bolus using 3D printing improves the bolus’s conformity to the irregular skin surface. This study aims to evaluate the physical characteristics and tissue-equivalent properties of HIPS filament and 3D-printed HIPS boluses at different thicknesses and infill densities. The physical characteristics of HIPS filament, including density, electron density, and Relative Electron Density (RED), were measured. At the same time, Fourier Transform Infrared (FTIR) spectroscopy was performed to determine the mass fraction percentages of polystyrene and polybutadiene. The 3D-printed HIPS boluses were characterized for bulk density, electron density, RED, water absorption percentage, internal pore size, and total pore volume, with bulk density and RED compared to those of adipose tissue. The physical characteristics of the HIPS filament showed a density of 1.01 g/cm3, an electron density of 3.29 × 1023 electrons/cm3, and a RED of 0.98, resembling those of adipose tissue. The physical characteristics of 3D-printed HIPS boluses at different infill densities showed bulk density ranging from 0.61 g/cm3 to 0.81 g/cm3, electron density ranging from 2.00×1023 electrons/cm3 to 2.63×1023 electrons/cm3, RED ranging from 0.59 to 0.79, and water absorption percentage ranging from 2.9% to 7.9%. The evaluation results showed that the 3D-printed HIPS bolus with a thickness of 0.6 cm and 80% infill density was the optimal configuration, exhibiting the lowest water absorption, smallest internal pore size and total pore volume, with bulk density and RED most similar to those of adipose tissue.